2010
DOI: 10.2193/2009-314
|View full text |Cite
|
Sign up to set email alerts
|

Cougar Kill Rate and Prey Composition in a Multiprey System

Abstract: Assessing the impact of large carnivores on ungulate prey has been challenging in part because even basic components of predation are difficult to measure. For cougars (Puma concolor), limited field data are available concerning fundamental aspects of predation, such as kill rate, or the influence of season, cougar demography, or prey vulnerability on predation, leading to uncertainty over how best to predict or interpret cougar-ungulate dynamics. Global Positioning System (GPS) telemetry used to locate predat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
156
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(184 citation statements)
references
References 32 publications
20
156
8
Order By: Relevance
“…We found that pumas killed a greater number of black-tailed deer in summer and autumn, which coincided with the birth pulse of fawns in summer. Past studies have hypothesized that increases in puma and gray wolf (Canis lupus L., 1758) kill rates during summer were due to increased availability of vulnerable young ungulates (Sand et al 2008;Knopff et al 2010;Metz et al 2012), and the number of fawns killed in summer and autumn in our study area supports this hypothesis. However, the notably lower handling times in summer and autumn may also have contributed to the increase in puma kill rates in summer and autumn and suggest that additional potential mechanisms may be influencing puma kill rates.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…We found that pumas killed a greater number of black-tailed deer in summer and autumn, which coincided with the birth pulse of fawns in summer. Past studies have hypothesized that increases in puma and gray wolf (Canis lupus L., 1758) kill rates during summer were due to increased availability of vulnerable young ungulates (Sand et al 2008;Knopff et al 2010;Metz et al 2012), and the number of fawns killed in summer and autumn in our study area supports this hypothesis. However, the notably lower handling times in summer and autumn may also have contributed to the increase in puma kill rates in summer and autumn and suggest that additional potential mechanisms may be influencing puma kill rates.…”
Section: Discussionsupporting
confidence: 84%
“…Ungulate migrations therefore result in significant redistributions of resources making it necessary for predators to respond to spatial and temporal variation in prey availability. Recent studies using GPS-collar technology have shown that top-level predators respond to seasonal variation in prey availability and vulnerability in numerous ways, including temporal changes in diet and species-specific kill rates (Sand et al 2008;Knopff et al 2010;Metz et al 2012;Elbroch et al 2013;Gervasi et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations